2010
DOI: 10.1007/s11832-010-0290-6
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of implementing the Ponseti method for correction of clubfoot in Vietnam

Abstract: Purpose To evaluate the short-term results of the non-surgical Ponseti method training programs run in Ho Chinh Minh City, Vietnam. Methods A questionnaire was developed and distributed to the 57 trainees who had completed one of the 3-day training courses. Results Of the 57 questionnaires distributed, 36 (63%) were completed and returned for evaluation. Most responders were continuing to use the Ponseti method for management of clubfoot. On average, each trainee had treated 16 babies with clubfoot, most of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(30 reference statements)
0
5
0
1
Order By: Relevance
“…The Ponseti method, including the use of FABs, was taught in a 3-day course in Vietnam, and a survey showed that 27 of 36 respondents were using the method after at least 12 months; 8 of the 9 respondents who were not using the method reported that they had not seen any clubfoot cases. 86 Measuring the results or effectiveness of technology transfer was not common, but is necessary, as was pointed out by the consensus documents discussed in Part One.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ponseti method, including the use of FABs, was taught in a 3-day course in Vietnam, and a survey showed that 27 of 36 respondents were using the method after at least 12 months; 8 of the 9 respondents who were not using the method reported that they had not seen any clubfoot cases. 86 Measuring the results or effectiveness of technology transfer was not common, but is necessary, as was pointed out by the consensus documents discussed in Part One.…”
Section: Resultsmentioning
confidence: 99%
“…The Ponseti method for clubfoot treatment, including the use of FABs, was investigated by several studies, although the main focus was not the FABs. The availability of FABs, 84,85 patient compliance with follow-up, 86 and compliance with the FAB protocol 65,87 were important in determining the outcome of the treatment. One study concluded that orthopedic clinical officers could effectively use the Ponseti method to treat clubfoot in Malawi 88 .…”
Section: Conclusion About Programs and Service Provisionmentioning
confidence: 99%
“…La prise en charge doit être idéalement hyperspécialisée car il est souvent nécessaire d'avoir recours à des interventions chirurgicales secondaires. [28,33,34], Ouganda [35,36], Vietnam [37][38][39], Chine [40], Nouvelle Zélande [27]. La formation des praticiens se fait lors de sessions d'apprentissage à la réalisation de plâtres correcteurs, sur quelques jours, regroupant un maximum de praticiens du pays.…”
Section: Bien Différentier Les Pieds Bots Atypiquesunclassified
“…Reaching rural areas was important, and distance from services was noted as a barrier to accessing them. 18,[102][103][104][105] Multi-disciplinary comprehensive services included physician services, physical therapy, social services, community outreach, vocational rehabilitation, and orthotics services. 104,106,107 The need for early screening/referral/fitting services was often mentioned for conditions of clubfoot 98,108,109 and scoliosis, 110 and it was recommended that CBR programs be used to facilitate this.…”
Section: Successful Service Provision Themes and Strategiesmentioning
confidence: 99%
“…13,103,105 Follow-up was noted as especially important for compliance with the Ponseti method for treatment of clubfoot. 98,100,103 Few authors discussed service provision specific to UE prosthetics. When it was discussed, the most common strategy was to be affordable.…”
Section: Successful Service Provision Themes and Strategiesmentioning
confidence: 99%